ANALISIS PENGARUH BRAND AWARENESS DAN BAURAN KOMUNIKASI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN ULANG PRODUK GADAI KCA MELALUI LOYALITAS KONSUMEN SEBAGAI VARIABEL INTERVENING DI PT PEGADAIAN CABANG MADIUN - Dwiningprihati, Restu Asih; Sugiarno, Yuventius (Jurnal Manajerial Bisnis, 2025)
This study aims to determine and analyze the effect of brand awareness and marketing communication mix on the decision to repurchase KCA pawn products through consumer loyalty as an intervening variable at PT Pegadaian Branch Madiun. The type of research used is quantitative research. The population used in this study were all customers who came to the Pegadaian Branch Madiun office who made KCA pawn transactions in April 2024. The sampling technique used in this study was multivariate technique with correlation or multiple regression. The data used in this study were obtained from questionnaires. Hypothesis testing uses descriptive statistics and data analysis using SmartPLS software, which is run on a computer. The results of this study indicate that Brand Awareness has a positive and significant effect on Repurchase Decisions and Consumer Loyalty, while Marketing Communication Mix has a positive and significant effect on Repurchase Decisions and Consumer Loyalty.